Facebook and self-regulation: Efficacious proposals – Or 'smoke-and-mirrors'?. (November 2021) - Hemphill, Thomas A.; Banerjee, Syagnik
Abstract: Facebook, Inc. has experienced controversies involving user privacy (the Cambridge Analytica data scandal), political manipulation (the 2016 and 2020 U S. elections), mass surveillance accusations, encouraging addiction and low self-esteem, and content integrity, such as fake news, conspiracy theories, copyright infringement, and hate speech. The nature of these controversies has led to Congressional scrutiny, as well as critics' calling for federal regulation of the company's activities. In 2020, Facebook released two company white papers: Charting a Way Forward: Online Content Regulation and Recommended Principles for Regulation or Legislation to Combat Influence Operations. Subsequently, a review of the key points of both these white papers is undertaken, followed by an analysis of issues confronting Facebook. The paper concludes with a proposed digital media regulatory framework recommending a three-pronged policy approach consisting of public regulation, private regulation, and industry liability reform, as well as implications for future academic research. Highlights: Facebook's previous efforts to combat online influence have fallen short. Facebook's proposed five principles is foundational for regulatory discussion. What it begs is the company's self-regulatory framework it implements. A digital media regulatory framework is proposed. It consists of public regulation, private regulation, and industry liability reform.